Early responses to Fe-deficiency distinguish Sorghum bicolor genotypes with contrasting alkalinity tolerance - Luna, Dario Fernando; Saavedra Pons, Amalia Beatriz; Bustos, Dolores Angela; Taleisnik, Edith (Elsevier, 2018)
Soil alkalinity is a significant limitation to agricultural productivity and it is associated to several soil features, among them, Fe deficiencies. In this work, we explored the hypothesis that alkalinity tolerance in Sorghum bicolor is related to Fe-deficiency tolerance and its underlying mechanisms. An initial screening involving 8 sorghum genotypes identified two with contrasting growth responses to alkalinity (susceptible Minu II and more tolerant Silero INTA Pemán) that were subsequently studied under Fe-deprivation (-Fe) conditions. Sorghum sudanense (sudangrass) was included as control tolerant species for Fe deficiency. Growth in hydroponics and in soil indicated that responses to both alkaline and -Fe substrates followed parallel trends in the three genotypes: Minu II was the most sensitive, followed by Silero and sudangrass. Decreases in carbon fixation (A) and stomatal conductance were observed earlier in -Fe than in alkalinity, and the intensity in the three genotypes followed the same tendency as growth depressions. Calculations derived from the analysis of A as a function of internal CO2 concentration (A/Ci curves) indicated increased Ci concentration along with a decrease in the efficiency of phosphoenol pyruvate caboxylase activity in Minu II. Fast chlorophyll a fluorescence transients (OJIP-test) revealed decreased PSII connectivity in both Minu II and Silero under -Fe, but Minu II disclosed more damage to the oxygen evolving complex under alkalinity, while sudangrass was largely unresponsive. Expression of the genes for phytosiderophore (Phys) synthesis and transport genes was induced under both alkalinity and -Fe conditions in both S. bicolor genotypes, and more strongly in Silero than in Minu II. Lower induction of gene expression in Minu II may be related to its sensitivity to alkalinity conditions associated to reduced Fe availability, leading to alteration in photochemical and biochemical reactions involving Fe. Thus, our results provide support to the concept that susceptibility to Fe-deficiency and alkalinity conditions are associated in Sorghum bicolor and highlight some of the physiological traits that underlie this association.